Problems of caste system in modern India - Taubaldieva, D. A.; Alipbayeva, B. A. (Journal of Oriental Studies, 2016)
This article focuses on the problems of the caste system in modern India. Subject of the caste system is very important. Despite the fact that officially confirmed that the caste system is no longer existent. Today, caste is part of the life of every Indian. The article examines the appearance of the caste system. Also author analysis the situation where cast groups are involved in politic life of the country.